Kebiasaan Mengunyah Sirih dan Kaitannya dengan Kondisi Periodontal: Tinjauan Naratif - Jasmine, Annisah Biancika; Flora, Rostika; J, Rahmi Fitri (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2024)
Background: Betel quid chewing is associated with the periodontal status, in which it may increase the risk and severity of periodontal disease. The objectives of this narrative review were to provide an overview of the literature about the association between betel quid chewing habit and periodontal status. Methods: The review analyzed several studies that examined the habit of betel quid chewing and its association with periodontitis in different populations. Results: Betel quid chewing was associated with a high prevalence of bleeding on sulcus probing, plaque index, gingival inflammation, deeper probing depth, and greater attachment loss. Additionally, the severity of periodontal disease was enhanced in subjects chewing betel quid with tobacco and alcohol consumption. Discussions: These results could be due to common components detected in the chewed substances and the synergistic effect between smoking and alcohol consumption with betel quid chewing habit. Conclusions: Prolonged and excessive use of betel quid can induce significant adverse effects on human health, including an increased risk of periodontitis. The findings of this review highlight the importance of addressing the impact of betel quid chewing on periodontal status.